Osteoporosis Therapy With Denosumab in Organ Transplant Recipients - Brunova, Jana; Kratochvilova, Simona; Stepankova, Jitka (Frontiers in Endocrinology, 2018)
Osteoporosis and fragility fractures represent serious complications for the solid organ transplant population. The recommended osteoporosis therapy for organ recipients involves supplementation with calcium and vitamin D and bisphosphonate administration. However, these options can prove limited for patients with impaired renal function. An alternative therapy option is offered by denosumab, a monoclonal antibody that targets RANKL (receptor activator of nuclear factor kappa-B ligand). Patients and Methods We evaluated 63 patients with osteoporosis (23 males and 40 females, age 56.4±13.1 years) following solid organ transplantation (15 diabetic patients after simultaneous transplantation of the kidney and pancreas, 34 patients after kidney transplantation and 14 patients with liver grafts). Osteoporosis was diagnosed according to standard DEXA examination using the Lunar Prodigy apparatus. Transplanted patients with impaired renal function were treated for osteoporosis of the L-spine and/or proximal femur with calcium and vitamin D supplementation and 60 mg of denosumab every 6 months between the years 2012 and 2017. The mean duration of the therapy was 1.65±0.7 years. Results After denosumab therapy, L-spine T-scores improved across the whole group, ranging from 2.7±0.09 to -1.8±1.0 (p<0.001). T-score values for the proximal femur increased from 2.5±0.8 to -2.0±0.7 after the therapy (p<0.01). We observed only a mild, statistically insignificant improvement in distal forearm T-scores. The mean increase in L-spine BMD was 11.5±6.2 % in subjects with osteoporosis at this site and 10.4±6.1 % in the case of all patients. BMD of the proximal femur increased by 10.4±8.3 % in patients with osteoporosis and by 7.5±7.3% in all patients. Denosumab therapy decreased the prevalence of osteoporosis in the L-spine from 75 % to 27 % (p<0.001) and proximal femur osteoporosis from 54 % to 36 % (p<0.05). Denosumab therapy reduced elevated levels of osteocalcin and beta-crosslaps (ßCTX) in comparison with baseline levels (p<0.001) across the whole group of graft recipients. Conclusions Denosumab therapy was well-tolerated and improved bone density in our group of solid organ transplant recipients. The indications are that denosumab could be a viable therapeutic option for transplanted patients with osteoporosis, especially in those with renal function impairment or bisphosphonate intolerance.